Surface topography analysis software validation - Todhunter, Luke (2020)
This thesis presents work in the field of surface texture analysis, focussing on improving the current state-of-the-art regarding the calculation of areal surface texture parameters by software. The work given in this thesis utilises the mathematical definitions of surface texture parameters to develop mathematically-defined reference values against which third-parties can compare, to assess the performance of their software.